2020
DOI: 10.3390/healthcare8030215
|View full text |Cite
|
Sign up to set email alerts
|

Korean Nursing Students’ First Experiences of Clinical Practice in Psychiatric Nursing: A Phenomenological Study

Abstract: Nursing students have a more negative attitude toward psychiatric practice than other practices. In particular, Korean nursing students experience increased pressure during clinical practice in psychiatric nursing due to sociocultural and institutional influences, such as prejudices, fear, and anxiety towards mental illnesses. This study aimed to conduct an investigation on students’ first experiences of clinical practice in psychiatric nursing. Participants were 12 fourth year nursing students in South Korea.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Furthermore, these experiences decreased students’ anxiety, allowing for greater confidence in nursing abilities and understanding of mental health nursing. Similarly, Cha et al. (2020) reported with continued experience, student nurses grow from the clinical experience, breaking down preconceived notions of mental illness, eventually feeling comfortable caring for and developing rapport with psychiatric patients.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Furthermore, these experiences decreased students’ anxiety, allowing for greater confidence in nursing abilities and understanding of mental health nursing. Similarly, Cha et al. (2020) reported with continued experience, student nurses grow from the clinical experience, breaking down preconceived notions of mental illness, eventually feeling comfortable caring for and developing rapport with psychiatric patients.…”
Section: Discussionmentioning
confidence: 94%
“…Research indicates that during mental health nursing clinicals, students initially experience barriers such as fear, anxiety, and distress. These may, in part, be due to a lack of experience, knowledge, understanding, and skills regarding mental health nursing, as well as preconceived notions regarding mental illness ( Brown, 2015 ; et al 2020 ; Happell, 1999 , 2008 ; Melrose & Shapiro, 1999 ). Psychiatric clinicals can be very emotional and may trigger a student's past trauma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other research studies also indicate that the students perceived individuals with mental disorders as less dangerous following the clinical practice [39,40]. In a qualitative study carried out in South Korea with nursing students, it was put forth that, in the context of psychiatric nursing, the students had emotional fluctuations and burnout at the beginning of the clinical practice whereas they experienced transformation and growth at the end of the clinical practice [41]. Also in some studies performed previously, it was found that the student nurses who took the psychiatric nursing course, spent time with the patients, or got in touch with standard patients through simulation method had a more positive attitude to the issue of stigmatization [29,[42][43][44][45].…”
Section: Conflicts Of Interestmentioning
confidence: 99%